The disconnect between visual assessment of air trapping and lung physiology for assessment of small airway disease in scleroderma-related interstitial lung disease: An observation from the Scleroderma Lung Study II Cohort. Issue 2 (June 2022) - Bae, Sangmee Sharon; Pourzand, Lila; Hyun Kim, Grace; Villegas, Bianca E; Oh, Andrea; Furst, Daniel E; Goldin, Jonathan; Tashkin, Donald P
Objective: To explore the presence of small airway disease (SAD) and emphysema in scleroderma-related interstitial lung disease (SSc-ILD) and to evaluate the physiologic and clinical correlates of SAD in SSc-ILD. Methods: Thoracic high-resolution computed tomography (HRCT) images obtained from the Scleroderma Lung Study II (SLSII) participants were reviewed by a group of thoracic radiologists. The presence of SAD was assessed by visual assessment for air trapping. HRCT scans were also evaluated for the presence of emphysema. The association of the presence of air trapping and emphysema with physiological measures of airway disease and clinical variables was evaluated. Results: A total of 155 baseline HRCT scans were reviewed. For assessment of air trapping, images needed to be adequate end-expiratory examinations, leaving 123 scans. Air trapping was seen in 13/123 (10.6%) of the SSc-ILD cohort and was independent of smoking history, asthma or the presence of gastroesophageal reflux. Air trapping on HRCT was not associated with physiologic evidence of SAD. We also identified 8/155 (5.2%) patients with emphysema on HRCT, which was independent of SAD and found mostly in prior smokers. Conclusion: We report the first study of air trapping on standardized, high-quality HRCT images as a reflection of SAD in a relatively large, well characterized SSc-ILD cohort. The presence of SAD in non-smoking SSc-ILD patients supports that SSc may cause not only restrictive lung disease (SSc-ILD), but also, to a lesser extent, obstructive disease. Physiologic measures alone may be inadequate to detect airway disease in patients with SSc-ILD.